Selective Voronoi tessellation as a method to design anisotropic and biomimetic implants - Deering, Joseph; Dowling, Kierdra I; DiCecco, Liza-Anastasia; McLean, Griffin D; Yu, Bosco; Grandfield, Kathryn (Elsevier, 2021)
The geometry of a metallic scaffold is important for the success of bone implants, where the introduction of porosity can reduce stress shielding effects and allow for bone tissue integration. In this work, porous scaffolds were designed to closely mimic the natural structure of trabecular bone using selective Voronoi tessellation with preferential seeding. A workflow to generate these structures is introduced, where voided regions of seeds in the starting volume create preferential texture during polyhedral expansion, resulting in modified strut orientation in the implant. Anisotropy was digitally characterized by mean-intercept length and star volume distribution measurements to determine similarity to trabecular orientation. This work demonstrates that selective Voronoi tessellation is an effective method to generate biomimetic porous scaffolds with increased anisotropy and tunable strut architecture in three dimensions as a suitable alternative to patient-derived bone geometries.
Keywords: Implant design; Biomimetics; Bone implants; Osseointegration; Additive manufacturing